Microwave assisted synthesis and photocatalytic activity of ZNS and CDS quantum dot systems - Soltani, Nayereh (2012)
Solar energy is an alternative sustainable energy resource that can be harvested using semiconductor quantum dots including zinc sulfide (ZnS) and cadmium sulfide (CdS). However, at present is only a small fraction of the sun’s energy (< 10%) absorbed by using pure ZnS and CdS semiconductor solar cells. To increase the overall photoactivity of these nanomaterials, various selective surface modifications can be used during synthesis process such as depositing the surface with organic or inorganic materials that causes charge transfer and electronic interaction between the surface attachment and the host semiconductor. In this work, pure ZnS and CdS quantum dots, PVP capped ZnS and CdS quantum dots, and ZnS/CdS and CdS/ZnS core shells were prepared by using the microwave irradiation technique involving water and polyol solvents. Pure ZnS and CdS semiconductor quantum dots were synthesized by both the Microwave-Hydrothermal (M-H) and Microwave-Polyol (M-P) methods, polymer-capped ZnS and CdS by the M-H method, and ZnS/CdS and CdS/ZnS core shells by the M-P method. The concentration of precursors was adjusted by varying the molar ratio of zinc and cadmium sources to sulfur source (1:1, 1:1.25, 1:1.5, and 1:2) in a fixed irradiation time (20 min). To study the effect of microwave irradiation, the reactions were carried out in 5, 10, 15, 20, 25, 30 and 40 min irradiation time using a pulse regime of 20% power (on for 5 s, off for 20 s). The formation of ZnS and CdS nanoparticles have been observed by the change in color of samples from colorless to white for ZnS nanoparticles and to yellow for CdS nanoparticles and confirmed by powder Xray diffraction (XRD). The crystal structure of ZnS and CdS nanocrystals synthesized in both the M-H and M-P method are cubic and hexagonal, respectively. The particle size of nanocrystals was determined using Scherrer’s equation from XRD spectra and transmission electron microscopy (TEM). The estimated average sizes in the M-H method are between 3.3 and 4.8 nm for ZnS and between 9.7 and 12.5 nm for CdS nanoparticles depending on the irradiation time. In the M-P method, the average sizes are between 3.2 and 4.9 nm for ZnS and between 8.9 and 11.4 nm for CdS. The size of nanoparticles was also calculated by the Brus formula according to the UV-Visible spectrum which agrees fairly well with those determined from the XRD spectra and TEM images. The optical band gap of ZnS and CdS nanoparticles was calculated from Tauc plot using UV-Visible spectra. The estimated band gaps of the M-H method samples are between 4.24 and 4.30 eV for ZnS and between 2.61 and 2.66 eV for CdS nanoparticles. For the M-P method, the optical band gaps are between 4.00 and 4.42 eV for ZnS, and between 2.62 and 2.67 eV for CdS. The blue shift of the absorption edge compared to that of bulk clearly explained the quantum confinement effect. Photoluminescence spectra of the samples all exhibited two individual peaks corresponding to zinc or cadmium vacancies and sulfur vacancies. The size of PVP-capped ZnS and CdS nanoparticles slightly increased compared to the bare ones. Consequently the absorption peaks shifted to higher wavelengths. The average particle sizes and estimated optical band gaps of synthesized nanoparticles in appropriate PVP concentration (5%) were 5.1 nm and 4.07 eV for ZnS and 18.3 nm and 2.53 eV for CdS. PL spectra of PVP-capped ZnS nanoparticles de-convoluted into three different bands which were attributed to zinc and sulfur vacancies, and surface trap states. PL spectra of PVP-capped CdS showed two green emission peaks related to cadmium and sulfur vacancies. The XRD spectra of ZnS/CdS and CdS/ZnS core shell nanoparticles were similar to the XRD pattern of the core materials. The estimated average sizes of ZnS/CdS core shell nanoparticles were 11.2 and 14.6 nm corresponding to shell thickness of 3.4 and 5.1 nm, respectively. For CdS/ZnS core shell nanoparticles the average particle sizes were 17.0 and 20.7 nm corresponding to shell thickness of 3.4 and 5.3 nm. The optical properties of ZnS/CdS and CdS/ZnS core shell nanoparticles in the visible region are dominated by CdS since its band gap is smaller than that of ZnS and both the conduction band and the valence band of CdS are located within the energy gap of ZnS. PL spectra of core shell nanoparticles de-convoluted into four different bands that could be attributed to zinc, cadmium and sulfur vacancies, and the radiative recombination of carriers at interfaces. The photocatalytic activity of the prepared nanoparticles was examined using dye degradation and water splitting for hydrogen production under illumination by a halogen lamp as a visible light source. To obtain the best condition of photocatalytic activity, samples were categorized in three groups. In the first group, pure ZnS and CdS nanoparticles were mixed together with ZnS:CdS weight ratios of (1:0), (0:1), (1:2), (2:1), (1:3), (3:1), (1:4) and (4:1). In the second group, PVP capped ZnS and CdS were mixed together with the same weight ratios of the first group and in the third one, photocatalytic activity of ZnS/CdS and CdS/ZnS core shells were examined. The results show that photocatalytic activity of samples in the first and second groups depends on the weight ratio of mixture. Using a typical 0.2 mg weight of photocatalyst quantum dots, the highest photocatalytic dye degradation rate after 120 min illumination in the three groups were 4.82 x 10-3, 9.15 x 10-3 and 7.56 x 10-3 min-1, respectively. In the water splitting reaction the maximum amount of hydrogen evolution after 6 hours in the three groups were 629, 736 and 1560 μmol respectively.